Selecting Large Portfolios of Social Projects in Public Organizations. (23rd April 2014) - Litvinchev, Igor; Lopez-Irarragorri, Fernando; Arratia-Martínez, Nancy Maribel; Marmolejo, José Antonio
Abstract : We address the portfolio selection of social projects in public organizations considering interdependencies (synergies) affecting project funds requirements and tasks. A mixed integer linear programming model is proposed incorporating the most relevant aspects of the problem found in the literature. The model supports both complete (all or nothing) and partial (a certain amount from a given interval of funding) resource allocation policies. Numerical results for large-scale problem instances are presented.